A prospective study of pattern of keloid and number of intralesional triamcinolone acetonide injections in a community based dermatology clinic in Lagos, Nigeria - Anaba, Ehiaghe L.; Akwara, Irene; Johnson, Omobolanle (International Journal of Research in Dermatology, 2019)
Background: Keloid a benign tumor of the skin is said to be common in Africans, Hispanics and Asians. Triamcinolone acetonide is a known treatment for keloid and patients come to the clinic asking how many times they need to come in for treatment. The number of times patients need to be injected is not clearly documented. The aim of this study was to document the socio-demographic factors, symptoms, clinical characteristics and determine how many times patients need to be injected with triamcinolone acetonide. Methods: This was a prospective descriptive study over a one year period in the outpatient Dermatology clinic of the General Hospital Lagos. Eighty six (86) patients were studied. Patients were clinically evaluated for keloid, a structured questionnaire for socio-demographic variables was administered to the patients. Patients were treated mainly with intralesional triamcinolone (40 mg/ml) every six weeks. Data was analyzed using the Epi-info 7. Results: There were 47 men and 39 women. The mean age of the patients was 33.18±13.37 years. Keloid was found to occur mainly in people aged 20-29 years (45.88%). The commonest anatomical location was the head and neck (45.88%) with multiple keloids in 44.70%. Patients were injected on the average 4 times irrespective of the length of keloid. Conclusions: Keloids are common, occur mostly in the third decade of life and require 3-5 injections of triamcinolone acetonide.